1983
DOI: 10.1017/s0022112083000324
|View full text |Cite
|
Sign up to set email alerts
|

Steady and oscillatory thermocapillary convection in liquid columns with free cylindrical surface

Abstract: In liquid columns (Prandtl number 8·9) with free cylindrical surface heated from above, strong thermocapillary convection (TC) has been observed. Stationary thermocapillary convection exists in the form of a single axially symmetric roll bound to the free surface. For aspect ratios l/a < 1 the radial extension of the roll equals the zone length. The stream velocities and the temperature distribution were measured.The influence of buoyant forces due to horizontal temperature gradients in the experiments was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(158 citation statements)
references
References 16 publications
11
146
0
1
Order By: Relevance
“…Experiments [2] performed with transparent liquids (with Prandtl numbers higher than those typical of liquid metals) have shown that for sufficiently small values of the Marangoni number, the convection in the liquid column is laminar, steady and axisymmetrical, but when the Marangoni number exceeds certain critical values depending on the Prandtl number of the liquid, on the geometry and on the boundary conditions, the liquid motion can undergo a transition to an oscillatory three-dimensional complex flow pattern. The appearance of these instabilities provides a possible explanation to justify the presence of undesirable macroscopic and microscopic imperfections in the final crystals obtained in microgravity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments [2] performed with transparent liquids (with Prandtl numbers higher than those typical of liquid metals) have shown that for sufficiently small values of the Marangoni number, the convection in the liquid column is laminar, steady and axisymmetrical, but when the Marangoni number exceeds certain critical values depending on the Prandtl number of the liquid, on the geometry and on the boundary conditions, the liquid motion can undergo a transition to an oscillatory three-dimensional complex flow pattern. The appearance of these instabilities provides a possible explanation to justify the presence of undesirable macroscopic and microscopic imperfections in the final crystals obtained in microgravity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…NaNO 3 , KCl, silicon oils) where the first instability is oscillatory (e.g. Preisser et al 1983;Velten, Schwabe & Scharmann 1991) and due to hydrothermal waves as discussed by Wanschura et al (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Variation of the aspect ratio Both experimental (Preisser et al 1983) and numerical studies (Wanschura et al 1995) pointed out that the critical wavenumber m is roughly proportional to the inverse aspect ratio 1/Γ of the half-zone since the azimuthal wavelength scales with the characteristic length d. As described in § 4.1 axial magnetic fields introduce a new, smaller length scale by reducing the radial extent of the thermocapillary flow. Thus, we would expect a tendency toward larger critical wavenumbers with increasing Hartmann number.…”
Section: 3mentioning
confidence: 98%
“…The three-dimensional supercritical flow is characterized by formation of a spatially organized pattern with integer number of pairs of hot and cold cells (see e.g., [3]). The properties of the wave are governed by the physical parameters of the system, such as strength of buoyancy [4,5], height of the column [6,7] and liquid volume [8,9]. In industrial applications related to crystal growth, the oscillatory thermocapillary convection was often accused of being responsible for periodic concentration variations in single crystals (see e.g., [10]).…”
Section: Introductionmentioning
confidence: 99%
“…In industrial applications related to crystal growth, the oscillatory thermocapillary convection was often accused of being responsible for periodic concentration variations in single crystals (see e.g., [10]). Aiming to understand the onset of oscillatory instability and suppress it, much efforts were put into studying convection in liquid bridge both theoretically [11][12][13] and experimentally [6,14]. The critical temperature difference, or suitably defined as the critical thermocapillary Reynolds number Re cr / DT cr , as well http://dx.doi.org/10.1016/j.ijheatmasstransfer.2014.02.058 0017-9310/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%